미국 식품안전관리제도 현황과 시사점 - 김재수 (주미대사관, 2006)
The purpose of this paper is to explore the U.S. food safety system and programs, and draw policy implications for Korea which now faces serious criticism from consumers. Following principles are important for the U.S. food safety system: 1) safe and wholesome food may be marketed; (2) regulatory decision-making in food safety be science-based; (3) the government's enforcement responsibility; and, (5) the regulatory process be transparent and accessible to the public. The lessons we learn from the U.S. food safety system are: 1) strict management of import inspection system; 2) enforcement of preventive measures; 3) efficient management of food safety administration; and, 4) increasing responsibility of food manufacturer and distributors. In addition, enforcement of current food safety programs including, country of origin, HACCP, tracebility, etc be equally important for the effective implementation of food safety programs.
Keywords: 식품안전제도; 수입검사; 농무부; 식품안전검사국; 식품의약청; food safety system; import inspection; USDA; FSIS; FDA